PINK1 autophosphorylation is required for ubiquitin recognition. (23rd February 2018) - Rasool, Shafqat; Soya, Naoto; Truong, Luc; Croteau, Nathalie; Lukacs, Gergely L; Trempe, Jean‐François
Abstract: Mutations in PINK1 cause autosomal recessive Parkinson's disease (PD), a neurodegenerative movement disorder. PINK1 is a kinase that acts as a sensor of mitochondrial damage and initiates Parkin‐mediated clearance of the damaged organelle. PINK1 phosphorylates Ser65 in both ubiquitin and the ubiquitin‐like (Ubl) domain of Parkin, which stimulates its E3 ligase activity. Autophosphorylation of PINK1 is required for Parkin activation, but how this modulates the ubiquitin kinase activity is unclear. Here, we show that autophosphorylation of Tribolium castaneum PINK1 is required for substrate recognition. Using enzyme kinetics and NMR spectroscopy, we reveal that PINK1 binds the Parkin Ubl with a 10‐fold higher affinity than ubiquitin via a conserved interface that is also implicated in RING1 and SH3 binding. The interaction requires phosphorylation at Ser205, an invariant PINK1 residue (Ser228 in human). Using mass spectrometry, we demonstrate that PINK1 rapidly autophosphorylates in trans at Ser205. Small‐angle X‐ray scattering and hydrogen–deuterium exchange experiments provide insights into the structure of the PINK1 catalytic domain. Our findings suggest that multiple PINK1 molecules autophosphorylate first prior to binding and phosphorylating ubiquitin and Parkin. Synopsis: The mitochondrial kinase PINK1 autophosphorylates rapidly in trans at a single conserved serine. This phosphorylation step is required for PINK1 to interact with its substrates ubiquitin and Parkin. PINK1 has a higher affinity for the Parkin ubiquitin‐like (Ubl) domain, which it binds via a surface conserved with ubiquitin. Insect PINK1 autophosphorylates in trans at Ser205 (Ser228 in human PINK1). Mutation of that serine strongly reduces ubiquitin and Parkin Ubl phosphorylation. Structural analysis of insect PINK1 in solution reveals that Ser205 phosphorylation induces significant changes in the dynamics of the protein near the active site. Abstract : The mitochondrial kinase PINK1 autophosphorylates rapidly in trans at a single conserved serine. This phosphorylation step is required for PINK1 to interact with its substrates ubiquitin and Parkin.